Promoting RNA editing by ADAR attraction - Danan-Gotthold, Miri (Genome Biol, 2017)
Concentration is important and not only while driving; a new study indicates how an adjacent genomic element helps to increase the efficiency of a specific adenosine to inosine RNA editing reaction, by providing a means to increase the local concentration of the RNA editing enzyme ADAR.